EFFECTIVENESS OF PUBLIC SERVICES AT THE POPULATION AND CIVIL REGISTRASION OFFICE OF WEST ACEH REGENCY - Hijraton Nazira; Ikhsan Ikhsan; Nodi Marefanda; Vellayati Hajad (DIA: Jurnal Administrasi Publik, 2021)
The aim of this paper is to assess the effectiveness of the public service provided to the community by the Department of Population and Civil Registry of West Aceh Regency. Department of Population and Civil Registry of West Aceh Regency is one of the elements of the implementation of the Local Government based on the Qanun above which is a regional technical institution that performs duties and functions of a corresponding authority which has already been established, namely by helping the Regent to carry out certain tasks in the field of administration. The qualitative method used in this research is the case study approach. The findings of this study are that the Western Aceh Disdukcapil government apparatus has been able to provide services to people in need of their services. This can be seen from the level of achievement of good results from the services provided to the community, which has saved time in the service delivery process and saved the cost of managing the community, Responding to needs and satisfaction, providing fair services without discrimination or discrimination on the basis of the principle of justice, maintaining good responsiveness to the community and providing services and completing services on time as promised by Disdukcapil officers.